A numerical study of coupled timber walls with slip friction damping devices. (15th September 2016) - Hashemi, Ashkan; Masoudnia, Reza; Quenneville, Pierre
Highlights: Coupled timber walls with slip-friction connections were introduced and numerically modelled. The response of the system to quasi-static and time-history dynamic loading was studied. The efficiency of the proposed system is compared with a similar system with equivalent nailplates. Timber coupled walls with slip friction connections enhance the ability of walls to absorb the seismic energy. Timber coupled walls with slip friction connections represent a feasible low damage solution for rocking timber structures. Abstract: In rocking timber structures, the traditional connections such as nailplates may need to be replaced by damping devices to provide the required lateral resistance and dissipate the seismic energy. This study seeks to investigate the seismic behaviour of coupled timber walls with slip friction connections. Slip friction connections present a low damage solution as they do not suffer from stiffness degradation and can be used after a seismic event. The seismic response of the described system is compared to those with equivalent nailplates. Displacement control quasi-static and also dynamic time-history analyses showed that the performance of the systems with friction devices is significantly improved under seismic loading compared to similar systems with equivalent nailplate connections. The systems with nailplates incurred significant inelastic damages while the systems with friction devices exhibited superior performance in terms of strength degradation and absorbed seismic energy. The introduced concept presents a feasible solution for timber structures when a low damage design is targeted.